Comparison of the Lamina Cribrosa Measurements Obtained by Spectral-Domain and Swept-Source Optical Coherence Tomography. (2nd September 2019) - Cakmak, Semih; Altan, Cigdem; Topcu, Husna; Arici, Murat; Pasaoglu, Isıl; Basarir, Berna; Solmaz, Banu
ABSTRACT: Purpose/Aim of the study : The aim of this study was to compare the lamina cribrosa (LC) measurements obtained by Spectral-Domain Optical Coherence Tomography (SD-OCT) and Swept-Source Optical Coherence Tomography (SS-OCT) in the same eye and we also investigate how the differences in measurement will change in the presence of pseudoexfoliation glaucoma (PEG). Materials and Methods : A total of 30 patients from one institution have accepted. Detailed medical case histories and clinical examination, optic nerve head imaging using the SD-OCT (Heidelberg Engineering, Heidelberg, Germany) and SS-OCT (Triton; Topcon Medical Systems, Tokyo, Japan) for patients with pseudoexfoliation glaucoma and healthy volunteer. Results : Fifty-three eyes of the 30 patients (13 female, 17 male) were included in the study. Twenty-nine of eyes were healthy and 24 of eyes had pseudoexfoliation glaucoma. The mean age was 62 ± 7.3 years (range, 50–86 years). The difference between the mean Bruch's membrane opening distance measured by SD-OCT (1504.7 ± 154.2 µm) and by SS-OCT (1568.6 ± 193.3 µm) was statistically significant (p = .009). The difference between LC depth and LC thickness measurements between two OCT devices were not statistically significant. There was a negative correlation between the difference of two devices Bruch's membrane opening distance measurements and the cup/disc ratio (p = .007). Conclusion : Generally accepted belief is that lamina cribrosa visibility would be worse in healthy subjects who have thick prelaminar tissues, and better in individuals with glaucoma who had suffered the loss of prelaminar tissue. The difference between Bruch's membrane opening distance measurements taken with two devices was greater in normal eyes, and this difference was decreasing in glaucomatous eyes in our study. The Lamina Cribrosa measurement values shall not be directly compared between SD-OCT and SS-OCT.